Negative electrode and all-solid-state battery
Patent Information
- Application Number
- JP2025061730
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-04-03
- Publication Date
- 2026-10-16
Smart Images

Figure 2026168560000001_ABST
Abstract
Description
[Technical Field]
[0001] This invention relates to a negative electrode and an all-solid-state battery. [Background technology]
[0002] Portable electronic devices are becoming smaller, lighter, thinner, and more multi-functional, thanks to the remarkable advancements in electronics technology. Batteries, which power these devices, are also in high demand for smaller size, lighter weight, thinner design, improved reliability, and enhanced safety. All-solid-state batteries, which use solid electrolytes, are attracting attention because they are safer than lithium-ion secondary batteries that use liquid electrolytes.
[0003] Solid electrolytes include oxide-based solid electrolytes, sulfide-based solid electrolytes, complex hydride-based solid electrolytes, halide-based solid electrolytes, and the like. For example, in Patent Document 1, A 2+a E 1-b+α G b D c X d A halide-based solid electrolyte represented by [formula] is disclosed. Compared to oxide-based solid electrolytes, sulfide-based solid electrolytes, complex hydride-based solid electrolytes, etc., halide-based solid electrolytes have high atmospheric stability, high voltage tolerance, and are easily adaptable to various processes.
[0004] Li4Ti5O is a suitable material for the negative electrode active material of all-solid-state batteries. 12 Lithium titanate is known. For example, in Patent Document 2, Li4Ti5O 12 In addition, negative electrode active materials have been disclosed that contain substances with a small proportion of plateau regions in the charge-discharge curve, thereby lowering resistance. Furthermore, for example, Patent Document 3 discloses a negative electrode active material that includes a composite material composed of titanium niobium oxide particles and a coating layer of lithium titanate particles formed on its surface, thereby suppressing the breakdown of titanium niobium oxide particles and improving cycle characteristics. [Prior art documents] [Patent Documents]
[0005] Patent Document 1 International Publication No. 2021 / 024785 Patent Document 2 Japanese Unexamined Patent Publication No. 2022-119324 Patent Document 3 Japanese Unexamined Patent Publication No. 2018-160432 Summary of Invention Problems to be Solved by the Invention
[0006] Li4Ti5O used in the negative electrode active material 12 has a small volume change associated with charging and discharging of all-solid-state batteries, and thus contributes to improvement of cycle characteristics of all-solid-state batteries. However, in an all-solid-state battery using Li4Ti5O as the negative electrode active material 12 , the charge-discharge potential is high, so that sufficient capacity and potential cannot be obtained, and it is difficult to increase the energy density.
[0007] Halide-based solid electrolytes have high ionic conductivity, can be handled in the atmosphere with high safety, and have plasticity, thus exhibiting high productivity. However, halide-based solid electrolytes are prone to reductive decomposition at low potentials. In an all-solid-state battery using a halide-based solid electrolyte, the halide-based solid electrolyte reacts with other electrode materials such as an active material at a low potential, which leads to deterioration of cycle characteristics. Therefore, the selection of materials for halide-based solid electrolytes is limited.
[0008] The present invention has been made in view of the above circumstances, and an object thereof is to provide a negative electrode for an all-solid-state battery and an all-solid-state battery that can achieve both high energy density and high cycle characteristics. Means for Solving the Problems
[0009] In order to solve the above problems, the present invention provides the following means.
[0010] (1) A negative electrode according to one aspect of the present invention includes a negative electrode active material containing TiNb₂O₇ as a main component, a solid electrolyte, and a conductive aid, wherein a surface of the negative electrode active material is coated with a coating layer containing a Li oxide, and the solid electrolyte contains Li a E b G c Cl d X e is a compound represented by (0.5≦a<6, 0<b<2, 0≦c≦6, 0<d≦6.1, 0≦e<6.1), and in the compound, E is one or more elements selected from the group consisting of Al, Sc, Y, Zr, Hf, and lanthanoids, and G is OH, BO₂, BO₃, BO₄, B₃O₆, B₄O₇, CO₃, NO₃, AlO₂, SiO₃, SiO₄, Si₂O₇, Si₃O₉, Si₄O 11 , Si₆O 18 , PO₃, PO₄, P₂O₇, P₃O 10 , SO₃, SO₄, SO₅, S₂O₃, S₂O₄, S₂O₅, S₂O₆, S₂O₇, S₂O₈, BF₄, PF₆, BOB, (COO)₂, N, AlCl₄, CF₃SO₃, CH₃COO, CF₃COO, OOC-(CH₂)₂-COO, OOC-CH₂-COO, OOC-CH(OH)-CH(OH)-COO, OOC-CH(OH)-CH₂-COO, C₆H₅SO₃, OOC-CH=CH-COO, C(OH)(CH₂COOH)₂COO, AsO₄, BiO₄, CrO₄, MnO₄, PtF₆, PtCl₆, PtBr₆, PtI₆, SbO₄, SeO₄, TeO₄, HCOO, and O, and X is one or more elements selected from the group consisting of F, Br, and I.
[0011] (2) In the negative electrode according to the above (1), the Li oxide may be one or more compounds selected from Li₃PO₄, Li₃BO₃, and Li₂SiO₃.
[0012] (3) In the negative electrode according to any one of the above (1) or (2), the ratio of the mass of the coating layer to the mass of the negative electrode active material is preferably 1.0 wt% or more and 3.0 wt% or less.
[0013] (4) In the negative electrode according to any one of the above (1) to (3), the median diameter of the particles constituting the negative electrode active material is preferably 3 μm or more and 16 μm or less.
[0014] (5) In the negative electrode according to any one of the above (1) to (4), the direct current resistance value is preferably 12 Ω or less.
[0015] (6) In the negative electrode according to any one of the above (1) to (4), the conductive auxiliary agent may include a carbon material.
[0016] (7) An all-solid-state battery according to one aspect of the present invention includes the negative electrode according to any one of the above (1) to (6). [Effects of the Invention]
[0017] According to the present invention, it is possible to provide a negative electrode for an all-solid-state battery and an all-solid-state battery that can achieve both high energy density and high cycle characteristics. [Brief Description of the Drawings]
[0018] [Figure 1] This is a schematic cross-sectional view of the all-solid-state battery according to the present embodiment. [Mode for Carrying Out the Invention]
[0019] Hereinafter, the present invention will be described in detail with appropriate reference to the drawings. The drawings used in the following description may, for convenience, show enlarged portions that are characteristic in order to make the features of the present invention easier to understand, and the dimensional ratios and the like of the respective constituent elements may differ from the actual ones. The materials, dimensions, and the like exemplified in the following description are merely examples, and the present invention is not limited thereto, and can be implemented with appropriate modifications within the scope that achieves the effects of the present invention.
[0020] "All-solid-state battery" Figure 1 is a schematic cross-sectional view of the all-solid-state battery 100 according to this embodiment. The all-solid-state battery 100 shown in Figure 1 comprises a power generation element 40 and an outer casing 50. The outer casing 50 covers the periphery of the power generation element 40. The power generation element 40 is connected to the outside via a pair of terminals 60 and 62. Although Figure 1 shows a stacked battery, a wound-type battery may also be used. The all-solid-state battery 100 can be used in, for example, laminated batteries, prismatic batteries, cylindrical batteries, coin-type batteries, button-type batteries, etc.
[0021] <Power generation element> The power generation element 40 comprises a solid electrolyte layer 10, a positive electrode 20, and a negative electrode 30. The power generation element 40 charges or discharges through the exchange of ions via the solid electrolyte layer 10 and electrons via an external circuit between the positive electrode 20 and the negative electrode 30.
[0022] (Negative electrode) As shown in Figure 1, the negative electrode 30 has a negative electrode current collector 32 and a negative electrode active material layer 34. The negative electrode active material layer 34 is in contact with the negative electrode current collector 32. The negative electrode active material layer 34 is located between the negative electrode current collector 32 and the solid electrolyte layer 10. The negative electrode 30 may be a single layer in which the materials constituting the negative electrode current collector 32 and the materials constituting the negative electrode active material layer 34 are mixed. The DC resistivity of the negative electrode 30 is preferably 12 Ω or less.
[0023] The negative electrode current collector 32 is electrically conductive. The negative electrode current collector 32 is, for example, a metal such as copper, aluminum, nickel, stainless steel, or iron, or a conductive resin. The negative electrode current collector 32 may be in the form of powder, foil, punched, or expanded.
[0024] The negative electrode active material layer 34 comprises a negative electrode active material, a solid electrolyte, and a conductive additive. The negative electrode active material layer 34 may also contain a binder.
[0025] The negative electrode active material mainly contains TiNb2O7 (titanium niobium oxide). The mass ratio of TiNb2O7 to the total negative electrode active material is 50% or more, preferably 60% or more, for example, 60% or more and 90% or less. TiNb2O7 can reversibly carry out the intercalation and release of lithium ions, and the insertion and deintercalation of lithium ions. By using a material containing TiNb2O7 as the negative electrode active material, Li4Ti5O 12 Compared to using LTO-type materials such as those mentioned above, the charge / discharge potential can be lowered and the charge / discharge capacity can be increased.
[0026] The negative electrode active material may include at least one of the following: a carbon material, a metal that can combine with lithium, an alloy, a composite material of a metal and a carbon material, an oxide, or metallic lithium. Examples of carbon materials include natural graphite, artificial graphite, mesocarbon microbeads, mesocarbon fiber (MCF), cokes, glassy carbon, and calcined organic compound bodies. Examples of metals that can combine with lithium include Si, Sn, and aluminum. Examples of oxides include SiO2. x Lithium titanate (Li4Ti5O 12 Examples include titanium niobium oxide (TiNb2O7), titanium dioxide (TiO2), and tin oxide (SnO2).
[0027] The median diameter of the particles constituting the negative electrode active material is, for example, 3 μm or more and 16 μm or less, preferably 4 μm or more and 14 μm or less, and more preferably 6 μm or more and 12 μm or less. If the median diameter is less than 3 μm, the capacity will decrease too much. If the median diameter is greater than 16 μm, the packing efficiency will decrease and the energy density will decrease.
[0028] The surface of the negative electrode active material is coated with a coating layer containing Li oxide (lithium oxide). The surface of the negative electrode active material refers to the surface of each TiNb2O7 particle that constitutes the negative electrode active material. The Li oxide is one or more compounds selected from, for example, Li3PO4, Li3BO3, and Li2SiO3.
[0029] The presence of a coating layer prevents the solid electrolyte from coming into contact with the surface of the negative electrode active material, thereby suppressing the degradation of the negative electrode active material due to side reactions with the solid electrolyte. As a result, the deterioration of the charge-discharge cycle characteristics of the all-solid-state battery caused by the degradation of the negative electrode active material can be suppressed.
[0030] The ratio of the mass of the coating layer to the mass of the negative electrode active material (coating amount) is preferably 1.0 wt% or more and 3.0 wt% or less, and more preferably 1.0 wt% or more and 2.5 wt% or less. The coverage area ratio of the coating layer to the surface of the negative electrode active material and the thickness of the coating layer are both proportional to the mass ratio of the coating layer.
[0031] If the mass ratio of the coating layer is less than 1.0 wt%, the surface area covered by the negative electrode active material decreases, and the thickness of the coating layer also decreases. In this case, areas of the negative electrode active material surface become exposed or nearly exposed, and the reaction with the solid electrolyte cannot be sufficiently suppressed. On the other hand, if the mass ratio of the coating layer is greater than 3.0 wt%, it is desirable in that the surface area covered increases, but the thickness of the coating layer increases too much, inhibiting lithium ion conduction and resulting in excessively high electrical resistance.
[0032] The solid electrolyte is a halide-based solid electrolyte containing Li, E, and Cl. The solid electrolyte contained in the negative electrode 30 is the conduction pathway for lithium ions within the negative electrode.
[0033] The solid electrolyte is Li a E b G c Cl d X e ...(1) is the compound represented by this formula.
[0034] a in Formula (1) represents the compositional ratio of Li in the compound represented by Formula (1). a satisfies 0.5≦a<6.0, preferably 1≦a≦4, and more preferably 1.5≦a≦3.5. In the solid electrolyte represented by Formula (1), when a satisfies 0.5≦a<6.0, the content of Li contained in the compound becomes appropriate, and the ionic conductivity of the solid electrolyte increases.
[0035] E in Formula (1) is one or more elements selected from the group consisting of Al, Sc, Y, Zr, Hf, and lanthanoids. E is an element that forms the skeleton of the halide-based solid electrolyte represented by Formula (1). The lanthanoids are La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu. The solid electrolyte containing E has a wide potential window and high ionic conductivity. E is more preferably any of Al, Sc, Y, Zr, Hf, and La, and further preferably Al or Zr.
[0036] b in Formula (1) represents the compositional ratio of E in the compound represented by Formula (1). b satisfies 0<b<2.0, preferably 0.3≦b≦1.5, and more preferably 0.6≦b≦1.3. E is an element with a higher density compared to other elements contained in Formula (1). An all-solid-state battery including a solid electrolyte that satisfies b≦1.0 has a low solid electrolyte density and a large capacity.
[0037] G in Formula (1) is substituted for a part of E that forms the skeleton of the solid electrolyte. The compound of Formula (1) may not contain G. G is, for example, OH, BO2, BO3, BO4, B3O6, B4O7, CO3, NO3, AlO2, SiO3, SiO4, Si2O7, Si3O9, Si4O 11 , Si6O 18 , PO3, PO4, P2O7, P3O 10It is at least one group selected from the group consisting of SO3, SO4, SO5, S2O3, S2O4, S2O5, S2O6, S2O7, S2O8, BF4, PF6, BOB, (COO)2, N, AlCl4, CF3SO3, CH3COO, CF3COO, OOC-(CH2)2-COO, OOC-CH2-COO, OOC-CH(OH)-CH(OH)-COO, OOC-CH(OH)-CH2-COO, C6H5SO3, OOC-CH=CH-COO, C(OH)(CH2COOH)2COO, AsO4, BiO4, CrO4, MnO4, PtF6, PtCl6, PtBr6, PtI6, SbO4, SeO4, TeO4, HCOO, and O. G is PO3, PO4, P2O7, P3O 10 Preferably, it is one or more groups selected from the group consisting of SO3, SO4, SO5, S2O3, S2O4, S2O5, S2O6, S2O7, S2O8, and O. These groups have a strong covalent bond with E. Therefore, when G is included, the E ion is less likely to be reduced, and the solid electrolyte is less likely to undergo reductive decomposition. Solid electrolytes containing G have a wide potential window on the reducing side and are less likely to be reduced.
[0038] In formula (1), c represents the composition ratio of G in the compound represented by formula (1). c is 0 ≤ c ≤ 6.0, preferably 0.2 ≤ c ≤ 5, and more preferably 0.5 ≤ c ≤ 3. Solid electrolytes containing G within this range have a wide potential window on the reducing side and are less susceptible to reductive decomposition. If the G content is too high, the ionic conductivity of the solid electrolyte decreases.
[0039] In formula (1), Cl and X are halide atoms. X is at least one element selected from the group consisting of F, Br, and I. Cl and X have large ionic radii per valence. Halide solid electrolytes represented by formula (1) have high ionic conductivity due to the presence of Cl or Cl and X, which facilitates the flow of lithium ions. Furthermore, halide solid electrolytes represented by formula (1) have high ionic conductivity and excellent oxidation and reduction resistance due to the presence of Cl.
[0040] d in Formula (1) represents the compositional ratio of Cl in the compound represented by Formula (1). d satisfies 0<d≦6.1, preferably 1≦d≦6, and more preferably 1≦d≦5. e in Formula (1) represents the compositional ratio of X in the compound represented by Formula (1). e satisfies 0≦e≦6.1, preferably 1≦e≦6, and more preferably 1≦e≦5. When d>0 or e>0 is satisfied, the strength of the pellet increases when the solid electrolyte is pressure-molded into a pellet form. Further, when d≧1.0 or e≧1.0 is satisfied, the ionic conductivity of the solid electrolyte increases. When d<6.1 and e<6.1 are satisfied, it is possible to avoid the situation where the content of Cl and X increases to cause a shortage of G and narrow the potential window of the solid electrolyte.
[0041] The halide-based solid electrolyte represented by Formula (1) is, for example, Li2ZrSO4Cl4, Li2ZrSO3Cl4, Li3ZrPO3Cl4, Li3ZrPO4Cl4, or the like.
[0042] The content of the solid electrolyte in the negative electrode active material layer 34 is not particularly limited, but based on the total mass of the negative electrode active material, the solid electrolyte, the conductive aid, and the binder, it is preferably 1 mass% or more and 50 mass% or less, and more preferably 5 mass% or more and 30 mass% or less.
[0043] The conductive aid includes, for example, a carbon material. The conductive aid may include, for example, carbon black, acetylene black, Ketjen black, graphite, carbon nanotubes, graphene, and the like. The conductive aid improves the electron conductivity of the negative electrode active material layer 34.
[0044] The median diameter of the conductive aid is, for example, 0.02 μm or more and 40 μm or less. The content of the conductive aid in the negative electrode active material layer 34 is not particularly limited. For example, based on the total mass of the negative electrode active material, the solid electrolyte, the conductive aid, and the binder, the mass ratio of the conductive aid is preferably 0.5 mass% or more and 20 mass% or less, and more preferably 1 mass% or more and 5 mass% or less.
[0045] The negative electrode active material layer 34 may contain a binder. The binder binds the negative electrode active material, solid electrolyte material, and conductive additive together within the negative electrode active material layer 34, and also firmly adheres the negative electrode active material layer 34 to the negative electrode current collector 32. The binder preferably has oxidation resistance and good adhesive properties.
[0046] Examples of binders used in the negative electrode active material layer 34 include polyvinylidene fluoride (PVDF) or its copolymer, polytetrafluoroethylene (PTFE), polyamide (PA), polyimide (PI), polyamideimide (PAI), polybenzimidazole (PBI), polyethersulfone (PES), polyacrylic acid (PA) and its copolymers, metal ion crosslinked polyacrylic acid (PA) and its copolymers, polypropylene (PP) grafted with maleic anhydride, polyethylene (PE) grafted with maleic anhydride, or mixtures thereof. Among these, PVDF is particularly preferred as the binder.
[0047] The binder content in the negative electrode active material layer 34 is not particularly limited, but is preferably 0.3% by mass or more and 10% by mass or less, and more preferably 0.3% by mass or more and 5% by mass or less, based on the total mass of the negative electrode active material, solid electrolyte, conductive additive and binder. If the amount of binder is too small, it tends not to be possible to form a negative electrode 30 with sufficient adhesive strength. Conversely, if the amount of binder is too large, since general binders are electrochemically inert, they do not contribute to the discharge capacity, and it tends not to be possible to obtain a sufficient volume or mass energy density. It should also be said that in the negative electrode active material layer 34, the remainder other than the solid electrolyte, conductive additive (carbon material) and binder is the negative electrode active material.
[0048] (positive electrode) As shown in Figure 1, the positive electrode 20 has a plate-shaped (foil-shaped) positive electrode current collector 22 and a positive electrode active material layer 24. The positive electrode active material layer 24 is in contact with at least one surface of the positive electrode current collector 22.
[0049] The material of the positive electrode current collector 22 can be any material that can withstand oxidation during charging and has good electrical conductivity that is resistant to corrosion. Examples of materials for the positive electrode current collector 22 include metals such as aluminum, stainless steel, nickel, and titanium, and conductive resins. The positive electrode current collector 22 may be in any of the following forms: powder, foil, punched, or expanded.
[0050] The positive electrode active material layer 24 contains a positive electrode active material and, if necessary, a solid electrolyte, a binder, and a conductive additive.
[0051] The positive electrode active material is not particularly limited as long as it is capable of reversibly carrying out the intercalation and deintercalation of lithium ions, and any positive electrode active material used in known all-solid-state batteries can be used. Examples of positive electrode active materials include lithium-containing metal oxides and lithium-containing metal phosphorus oxides.
[0052] Lithium-containing metal oxides include, for example, lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese spinel (LiMn2O4), and LiNi, which have the general formula: LiNi x Co y Mn z Composite metal oxides represented by O2(x+y+z=1), lithium vanadium compounds (LiVOPO4, Li3V2(PO4)3), olivine-type LiMPO4 (where M represents at least one selected from Co, Ni, Mn, and Fe), lithium titanate (Li4Ti5O 12 ) etc.
[0053] Furthermore, the positive electrode active material may not contain lithium. Examples of such positive electrode active materials include lithium-free metal oxides (MnO2, V2O5, etc.), lithium-free metal sulfides (MoS2, etc.), and lithium-free fluorides (FeF3, VF3, etc.). When using a lithium-free positive electrode active material, the negative electrode should be doped with lithium ions beforehand, or a negative electrode containing lithium ions should be used.
[0054] The positive electrode active material layer 24 may contain a solid electrolyte. The solid electrolyte is, for example, the solid electrolyte described above. Alternatively, the solid electrolyte contained in the positive electrode active material layer 24 may be a known solid electrolyte different from the solid electrolyte described above.
[0055] The content of the solid electrolyte in the positive electrode active material layer 24 is not particularly limited, but is preferably 1% by mass or more and 50% by mass or less, and more preferably 5% by mass or more and 30% by mass or less, based on the total mass of the positive electrode active material, solid electrolyte, conductive additive and binder.
[0056] The positive electrode active material layer 24 may contain a binder. The binder binds the positive electrode active material, solid electrolyte material, and conductive additive together within the positive electrode active material layer 24, and also firmly adheres the positive electrode active material layer 24 to the positive electrode current collector 22. It is preferable that the positive electrode active material layer 24 contains a binder. It is preferable that the binder has oxidation resistance and high adhesiveness. The binder contained in the positive electrode active material layer 24 is the same as the binder contained in the negative electrode 30.
[0057] The positive electrode active material layer 24 may contain a conductive additive. The conductive additive improves the electronic conductivity of the positive electrode active material layer 24. The conductive additive may be the same as or different from the one used in the negative electrode active material layer 34. Examples of conductive additives include carbon materials such as carbon black, graphite, carbon nanotubes, and graphene; metals such as aluminum, copper, nickel, stainless steel, iron, and amorphous metals; conductive oxides such as ITO; or mixtures thereof. The conductive additive may be in the form of a powder or fibers.
[0058] The content of the conductive additive in the positive electrode active material layer 24 is not particularly limited. When a conductive additive is added, the mass ratio of the conductive additive is usually preferably 0.5% by mass or more and 20% by mass or less, and more preferably 1% by mass or more and 5% by mass or less, based on the total mass of the positive electrode active material, solid electrolyte, conductive additive, and binder.
[0059] (solid electrolyte layer) The solid electrolyte layer 10 is sandwiched between the positive electrode 20 and the negative electrode 30. The solid electrolyte layer 10 contains a solid electrolyte that can move ions by an externally applied voltage. For example, the solid electrolyte conducts lithium ions and inhibits electron movement.
[0060] The material of the solid electrolyte layer 10 is, for example, a halide-based solid electrolyte. The solid electrolyte layer 10 contains, for example, the solid electrolyte described above. The solid electrolyte contained in the solid electrolyte layer 10 may be different from the solid electrolyte described above.
[0061] The solid electrolyte layer 10 may contain a binder or the like in addition to the solid electrolyte. The binder can be the same type used in the positive electrode 20 or the negative electrode 30.
[0062] <Exterior> The outer casing 50 houses the power generation element 40 inside. The outer casing 50 prevents moisture and other elements from entering the interior from the outside. The outer casing 50 has, for example, a metal foil 52 and resin layers 54 laminated on each surface of the metal foil 52, as shown in Figure 1. The outer casing 50 is a metal laminate film in which the metal foil 52 is coated on both sides with resin layers 54.
[0063] The metal foil 52 is, for example, aluminum foil or stainless steel foil. As the resin layer 54, for example, a resin film such as polypropylene can be used. The materials constituting the resin layer 54 may be different on the inside and outside. For example, a polymer with a high melting point, such as polyethylene terephthalate (PET) or polyamide (PA), can be used as the outer material, and polyethylene (PE) or polypropylene (PP) can be used as the inner material.
[0064] <Terminal> Terminals 60 and 62 are connected to the negative electrode 30 and the positive electrode 20, respectively. Terminal 62, connected to the positive electrode 20, is the positive terminal, and terminal 60, connected to the negative electrode 30, is the negative terminal. Terminals 60 and 62 are responsible for electrical connections to the outside. Terminals 60 and 62 are made of conductive materials such as aluminum, nickel, and copper. The connection method may be welding or screw fastening. It is preferable to protect terminals 60 and 62 with insulating tape to prevent short circuits.
[0065] [Manufacturing method for all-solid-state batteries] The positive electrode 20 is prepared. The positive electrode 20 is manufactured by applying a paste containing the positive electrode active material onto the positive electrode current collector 22 and forming a positive electrode active material layer 24 by firing or drying (natural drying). The above-mentioned solid electrolyte and the above-mentioned conductive additive may be added to the paste containing the positive electrode active material.
[0066] The negative electrode 30 is prepared. The negative electrode 30 is manufactured by applying a paste containing the negative electrode active material and the coating layer material (mixed material) onto the negative electrode current collector 32, and then firing or drying (natural drying) to form a negative electrode active material layer 34 with a coated surface. The above-mentioned solid electrolyte and the above-mentioned conductive additive may be added to the paste containing the negative electrode active material.
[0067] When firing, it is preferable to set the firing temperature to 800°C or higher and 1200°C or lower, and the firing time to 0.5 hours or higher and 5 hours or lower. When drying, it is preferable to dry at room temperature (around 20°C to 30°C, preferably 25°C) for a drying time of 4 hours or higher and 18 hours or lower. Firing or drying after pasting promotes the crystal growth or coating of Li oxide contained in the coating layer material, respectively. Therefore, the amount of coating is proportional to the temperature and time of firing or drying after pasting. That is, the higher the firing or drying temperature, and the longer the firing or drying time, the greater the coating.
[0068] The coating amount is preferably adjusted so that the DC resistance of the negative electrode is 12 Ω or less, preferably between 0.05 Ω and 8 Ω, and more preferably between 0.05 Ω and 5 Ω. The DC resistance of the negative electrode can be measured, for example, by sandwiching the manufactured negative electrode 30 powder between two electrodes without pressurizing (in an unrestrained state) and applying a voltage between the electrodes.
[0069] The power generation element 40 can be manufactured, for example, using a powder molding method. A guide with holes is placed on the positive electrode 20, and a solid electrolyte is filled into the guide. Then, the surface of the solid electrolyte is smoothed, and the negative electrode 30 is placed on top of the solid electrolyte. At this stage, the solid electrolyte is sandwiched between the positive electrode 20 and the negative electrode 30. Then, pressure is applied to the positive electrode 20 and the negative electrode 30 to pressure mold the solid electrolyte. This pressure molding yields a laminate in which the positive electrode 20, the solid electrolyte layer 10, and the negative electrode 30 are stacked in that order.
[0070] Next, external terminals are welded to the positive electrode current collector 22 of the positive electrode 20 and the negative electrode current collector 32 of the negative electrode 30, respectively, using a known method, thereby electrically connecting the positive electrode current collector 22 or the negative electrode current collector 32 to the external terminals. After that, the laminate connected to the external terminals is housed in the outer casing 50, and the opening of the outer casing 50 is sealed by heat sealing. Through these steps, the all-solid-state battery 100 of this embodiment is obtained.
[0071] As described above, in the all-solid-state battery 100 according to this embodiment, the negative electrode active material constituting the negative electrode 30 contains TiNb2O7 as the main component, which allows for a lower charge / discharge potential of the negative electrode and a larger capacity, thereby improving energy density. Furthermore, in the all-solid-state battery 100 according to this embodiment, the surface of the negative electrode active material constituting the negative electrode 30 is covered with a coating layer containing Li oxide, which prevents side reactions between the halide-based solid electrolyte, which undergoes reductive decomposition at low potential, and the negative electrode active material. As a result, degradation of the negative electrode active material during charge / discharge due to side reactions can be prevented, and good cycle characteristics can be maintained. Therefore, the all-solid-state battery 100 using the negative electrode of this embodiment can achieve both high energy density and high cycle characteristics.
[0072] Although embodiments of the present invention have been described in detail above with reference to the drawings, the configurations and combinations thereof in each embodiment are merely examples, and additions, omissions, substitutions, and other modifications to the configurations are possible without departing from the requirements of the present invention. [Examples]
[0073] "Example 1" In Example 1, a charge / discharge half-cell was fabricated, and its rate characteristics and cycle characteristics were measured. The charge / discharge half-cell in Example 1 was fabricated using the following procedure.
[0074] The half-cells for charging and discharging were fabricated in a glove box with a dew point of approximately -70°C and circulating argon gas. A lower punch was inserted into a PEEK cylinder of the pellet fabrication jig, and 110 mg of solid electrolyte Li2ZrSO4Cl4 was placed on top of the lower punch.
[0075] The pellet manufacturing jig consists of a PEEK (polyetheretherketone) cylinder with an outer diameter of 30 mm, an inner diameter of 10 mm, and a height of 20 mm, and an upper punch and a lower punch with a diameter of 9.99 mm. The upper and lower punches are made of die steel (SKD11 material).
[0076] The solid electrolyte was prepared using the following procedure. In a glove box under an Ar gas atmosphere, lithium sulfate (Li2SO4) and zirconium chloride (ZrCl4) were weighed out in a molar ratio of 1:1 as raw material powders. The raw material powders were then placed into a sealed zirconia container for a planetary ball mill, which already contained zirconia balls.
[0077] Next, a lid was placed over the airtight container, the lid was screwed to the container body, and the gap between the lid and the container was further sealed with polyimide tape. Polyimide tape has the effect of blocking moisture. Next, the zirconia airtight container was set in a planetary ball mill. The raw material powder was subjected to a mechanochemical reaction for 24 hours under conditions of a rotational speed of 500 rpm and an orbital speed of 500 rpm (the direction of rotation and the direction of revolution were opposite).
[0078] Next, a PEEK cylinder was vibrated to level the surface of the solid electrolyte. Then, an upper punch was inserted onto the solid electrolyte and pressed with a press machine under a load of 373 MPa to form a solid electrolyte layer.
[0079] Next, the upper punch was removed, and 15 mg of the negative electrode mixture was added on top of the solid electrolyte layer. The negative electrode mixture contained the negative electrode active material, the aforementioned solid electrolyte, and a conductive additive in the ratio negative electrode active material:solid electrolyte:conductive additive = 70 wt%:25 wt%:5 wt%. The negative electrode mixture was obtained by mixing these raw materials in an agate mortar for 15 minutes. The negative electrode active material was titanium niobium oxide (TiNb2O7) coated with 1.5 wt% Li3PO4.
[0080] Next, a PEEK cylinder was vibrated to smooth the surface of the negative electrode mixture. Then, an upper punch was inserted onto the negative electrode mixture and pressed with a press machine at a load of 373 MPa. Next, the lower punch was removed, a lithium foil with a diameter of 10 mm and a thickness of 100 μm was placed on top of the solid electrolyte layer, and the lower punch was inserted. The half-cell configuration is negative electrode mixture layer / solid electrolyte layer / Li foil.
[0081] In addition, two stainless steel plates with a diameter of 50 mm and a thickness of 5 mm, and two Bakelite® plates with a diameter of 50 mm and a thickness of 2 mm were prepared. Next, four holes for screws were made in each of the two stainless steel plates and the two Bakelite® plates. The holes for the screws were positioned so that when the half cell and the two stainless steel plates and the two Bakelite® plates are stacked, the two stainless steel plates and the two Bakelite® plates overlap in a plan view, but do not overlap with the half cell in a plan view.
[0082] Subsequently, stainless steel plates, bakelite® plates, half cells, bakelite® plates, and stainless steel plates were stacked in this order, and screws were inserted into the screw holes and tightened with a torque of 1 N·m. In this way, a half cell was obtained in which the upper and lower punches of the electrochemical cell were insulated by bakelite® plates. Next, the half cell was left to stand in a 25°C constant temperature bath for 48 hours to stabilize the open-circuit voltage.
[0083] The half-cell of Example 1 was charged and discharged under the following conditions, and the initial charge-discharge efficiency was measured. The charge-discharge, charge capacity, and discharge capacity measurements in the charge-discharge test were performed using the BCS805 charge-discharge device (product name; manufactured by Biologic).
[0084] The rate characteristics were calculated using the discharge capacity at a rate of 0.05C and a rate of 1C, according to the following formula. Rate characteristic (%) = (Discharge capacity at 1C rate (mAh) / Discharge capacity at 0.05C rate (mAh) × 100)
[0085] In the charge-discharge test of rate characteristics, charging was 1V (vs. Li / Li). + ) is performed up to 3V (vs.Li / Li) and discharge is 3V (vs.Li / Li +The test was conducted up to 0.05C (the current value at which charging is completed in 20 hours when constant current charging is performed at 25°C). The discharge rates were set to 0.05C (the current value at which discharge is completed in 20 hours when constant current discharge is performed at 25°C) and 1C (the current value at which discharge is completed in 1 hour when constant current discharge is performed at 25°C).
[0086] The cycle characteristics were calculated using the discharge capacity of the first cycle (initial discharge capacity) and the discharge capacity of the 100th cycle, according to the following formula. Cycle performance (%) = (Discharge capacity at 100th cycle (mAh) / Discharge capacity at 1st cycle (mAh) × 100)
[0087] In the charge-discharge cycle characteristic test, charging was performed up to 1V (vs. Li / Li+), and discharging was performed up to 3V (vs. Li / Li+). The charge rate and discharge rate were set to 0.2C (the current value at which charging or discharging is completed in 5 hours when constant current charging or discharging is performed at 25°C).
[0088] Examples 2-28 By changing the particle size of the solid electrolyte and negative electrode active material, the coating material and its coating amount within the scope of the above embodiment, a half-cell for charging and discharging was prepared in the same manner as in Example 1, and the charging and discharging efficiency was measured.
[0089] "Comparative Examples 1-12" The amount of coating material covering the negative electrode active material was changed outside the scope of the above embodiment, and a half-cell for charging and discharging was prepared in the same manner as in Example 1, and the charging and discharging efficiency was measured.
[0090] The conditions and cycle characteristics of the half-cells for Examples 1-28 and Comparative Examples 1-12 are summarized in the table below. The cycle characteristics are defined as the maintenance rate of the charge-discharge efficiency after 100 cycles relative to the initial charge-discharge efficiency.
[0091] [Table 1]
[0092] In Examples 1 to 28, high cycle characteristics were obtained in all cases. This is thought to be because the surface of the negative electrode active material was covered with a coating layer in the range of 1.0 wt% to 3.0 wt%, suppressing side reactions between the negative electrode active material and the solid electrolyte. On the other hand, in Comparative Examples 1 to 12, the cycle characteristics were reduced. The reduction in cycle characteristics in Comparative Examples 1, 2, 4, 5, 7, 8, 10, and 11 is thought to be because the amount of the coating layer was less than 1.0 wt%, resulting in areas on the surface of the negative electrode active material being exposed or nearly exposed, and thus the reaction with the solid electrolyte could not be sufficiently suppressed. Furthermore, the reduction in cycle characteristics in Comparative Examples 3, 6, 9, and 12 is thought to be because the thickness of the coating layer was too high, inhibiting lithium ion conduction and resulting in excessively high electrical resistance. [Industrial applicability]
[0093] The negative electrode for all-solid-state batteries of this embodiment is suitably applied to all-solid-state batteries containing a halide-based solid electrolyte. [Explanation of symbols]
[0094] 10 Solid electrolyte layer 20 positive electrode 22 Positive electrode current collector 24 Cathode active material layer 30 negative electrode 32 Negative electrode current collector 34 Negative electrode active material layer 40 Power generation element 50 Exterior 52 Metal foil 54 Resin layer Terminals 60, 62
Claims
1. TiNb 2 O 7 It comprises a negative electrode active material mainly composed of a solid electrolyte and a conductive additive, The surface of the negative electrode active material is covered with a coating layer containing Li oxide. The solid electrolyte is Li a E b G c Cl d X e It is a compound represented by (0.5 ≤ a < 6, 0 < b < 2, 0 ≤ c ≤ 6, 0 < d ≤ 6.1, 0 ≤ e < 6.1), In the aforementioned compound, E is one or more elements selected from the group consisting of Al, Sc, Y, Zr, Hf, and lanthanides. GはOH、BO 2 、BO 3 、BO 4 、B 3 O 6 、B 4 O 7 、CO 3 、NO 3 、AlO 2 、SiO 3 、SiO 4 、Si 2 O 7 、Si 3 O 9 、Si 4 O 11 、Si 6 O 18 、PO 3 、PO 4 、P 2 O 7 、P 3 O 10 、SO 3 、SO 4 、SO 5 、S 2 O 3 、S 2 O 4 、S 2 O 5 、S 2 O 6 、S 2 O 7 、S 2 O 8 、BF 4 、PF 6 、BOB、(COO) 2 、N、AlCl4、CF 3 SO 3 、CH 3 COO、CF 3 COO、OOC-(CH 2 ) 2 -COO、OOC-CH 2 -COO、OOC-CH(OH)-CH(OH)-COO、OOC-CH(OH)-CH 2 -COO、C6H 5 SO 3 、OOC-CH=CH-COO、C(OH)(CH 2 COOH) 2 COO、AsO 4 、BiO 4 ,CrO 4 MnO 4 , PtF 6 , PtCl 6 , PtBr 6 , PtI 6 SbO 4 SeO 4 TeO 4 It is one or more groups selected from the group consisting of HClO and O. X is one or more elements selected from the group consisting of F, Br, and I, and is the negative electrode.
2. The Li oxide is Li 3 PO 4 Li 3 BO 3 Li 2 SiO 3 The negative electrode according to claim 1, which is one or more compounds selected from the following.
3. The negative electrode according to claim 1, wherein the ratio of the mass of the coating layer to the mass of the negative electrode active material is 1.0 wt% or more and 3.0 wt% or less.
4. The negative electrode according to claim 1, wherein the median diameter of the particles constituting the negative electrode active material is 3 μm or more and 16 μm or less.
5. The negative electrode according to claim 1, wherein the DC resistance is 12 ohms or less.
6. The negative electrode according to claim 1, wherein the conductive additive comprises a carbon material.
7. A solid-state battery comprising the negative electrode described in any one of claims 1 to 6.
Citation Information
Patent Citations
Negative electrode active material composite for lithium ion secondary battery and method of manufacturing the same
JP2018160432A
Negative electrode active material layer
JP2022119324A
Solid electrolyte, solid electrolyte layer, and solid electrolyte cell
WO2021024785A1